Analisis Penggunaan Media Matching Gambar dan Mufrodat Bahasa Arab Perspektif Moh. Uzer Usman - Khairani, Riska; Loka, Fitrah; Mubarak, Muhammad Zaki (Prosiding Konferensi Nasional Bahasa Arab, 2023)
This research was conducted to analyze how teachers use picture matching and mufrodat game media in the classroom based on Moh's perspective. Uzer Usman whose goal is to make students active and enthusiastic in learning Arabic and the class atmosphere is no longer monotonous. This research was conducted with an interpretive paradigm, using a qualitative approach with a case study method. This research was carried out at Mtsn 4 Panyabungan. The data sources in this research are 8th grade Arabic teachers, 8th grade students c. Data collection was carried out by observation, interviews and documentation. The population in this study was students of class 8 Mtsn 4 Panyabungan, the sample was class 8 C. The strategies used by researchers were interviews, observation and documentation. The results of this research show that the use of image matching game media and mufrodat based on Moh Uzer Usman's indicators has not been fully implemented. 6 of the 9 indicators have been met, while the sections on reminding students of learning competencies and providing feedback have not been implemented by teachers.